Low Relative Skeletal Muscle Mass (Sarcopenia) in Older Persons Is Associated with Functional Impairment and Physical Disability - Janssen, Ian; Heymsfield, Steven B.; Ross, Robert (Journal of the American Geriatrics Society (JAGS), 2002)
OBJECTIVES: To establish the prevalence of sarcopenia in older Americans and to test the hypothesis that sarcopenia is related to functional impairment and physical disability in older persons. DESIGN: Cross‐sectional survey. SETTING: Nationally representative cross‐sectional survey using data from the Third National Health and Nutrition Examination Survey (NHANES III). PARTICIPANTS: Fourteen thousand eight hundred eighteen adult NHANES III participants aged 18 and older. MEASUREMENTS: The presence of sarcopenia and the relationship between sarcopenia and functional impairment and disability were examined in 4,504 adults aged 60 and older. Skeletal muscle mass was estimated from bioimpedance analysis measurements and expressed as skeletal muscle mass index (SMI = skeletal muscle mass/body mass × 100). Subjects were considered to have a normal SMI if their SMI was greater than ‐one standard deviation above the sex‐specific mean for young adults (aged 18–39). Class I sarcopenia was considered present in subjects whose SMI was within ‐one to ‐two standard deviations of young adult values, and class II sarcopenia was present in subjects whose SMI was below ‐two standard deviations of young adult values. RESULTS: The prevalence of class I and class II sarcopenia increased from the third to sixth decades but remained relatively constant thereafter. The prevalence of class I (59% vs 45%) and class II (10% vs 7%) sarcopenia was greater in the older (≥ 60 years) women than in the older men (P < .001). The likelihood of functional impairment and disability was approximately two times greater in the older men and three times greater in the older women with class II sarcopenia than in the older men and women with a normal SMI, respectively. Some of the associations between class II sarcopenia and functional impairment remained significant after adjustment for age, race, body mass index, health behaviors, and comorbidity. CONCLUSIONS: Reduced relative skeletal muscle mass in older Americans is a common occurrence that is significantly and independently associated with functional impairment and disability, particularly in older women. These observations provide strong support for the prevailing view that sarcopenia may be an important and potentially reversible cause of morbidity and mortality in older persons.